Enhancing problem list documentation in electronic health records using two methods: the example of prior splenectomy. Issue 1 (28th July 2017) - McEvoy, Dustin; Gandhi, Tejal K; Turchin, Alexander; Wright, Adam
Abstract : Background: Quality improvement professionals often choose between patient-specific interventions, like clinical decision support (CDS), and population-based interventions, like registries or care management. In this paper, we explore the synergy of these two strategies, targeting the problem of procedure documentation for patients with a history of splenectomy. Methods: We developed a population health documentation (PHD) intervention and a CDS intervention to improve splenectomy documentation within our electronic health record. Rates of splenectomy documentation were collected before and after the implementation of both interventions to assess their impact on the rate of procedure documentation. Results: Both the PHD and CDS interventions led to statistically significant (p<0.001) increases in the baseline rate of splenectomy documentation of 27.4 documentations per month. During the PHD intervention, 444.7 splenectomies were documented per month, while 40.8 splenectomies per month were documented during the CDS intervention. Discussion: Both approaches were successful, with the PHD intervention leading to a larger number of incremental procedure documentations, in batches, and the CDS intervention augmenting procedure documentation on an ongoing basis. Our results suggest that population health and CDS strategies complement each other and, where possible, should be used in conjunction. Conclusions: PHD and CDS strategies may best be used in conjunction to create a symbiotic relationship in which current problem and procedure documentation gaps are closed using PHD strategies, while new gaps are prevented through ongoing CDS interventions